PCBs and DDTs in surface mangrove sediments from the south of Iran (ID NO. 048) - Mohebbi Nozar, S. L.; Ismail, Wan Ruslan; Zakaria, Mohamad Pauzi; Mortazawi, Mohammad Seddiq (Graduate Faculty of Environment, University of Tehran, 2013)
Mangrove sediments were collected during wet and dry seasons from nine stations in Khamir, Laft and natural reservoir mangrove-dense areas of Hormozgan province in the south of Iran. Σ PCBs ranged from 5.33 to 15.5 ng/g dry weight and the dominant congener was no.153. Average Σ DDTs for Khamir and Laft mangroves were 16.58 ± 1.51 and 18.8 ± 9.98 ng/g dry weight. DDT was more abundant than DDE and DDD isomers, which indicated the input of DDT. The sediment quality guideline shows that the concentration of Σ PCBs were below the ER-M guideline, whereas levels of Σ DDTs were between ER-L and ER-M. The mangrove ecosystem in Hormozgan province is suffering from urban and industrial development.